2017
DOI: 10.17265/1548-6648/2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of HIV Transmission in Nasarawa State, Nigeria: An Analysis of Distribution of New Infections

Abstract: The need to understand local HIV epidemics and linking the prevention and other interventions to evidences become very important for the success of HIV response. The objective of the study was to estimate the distribution of new HIV infections among adult population (15-49 yrs) and to identify the groups at highest risk of HIV infection in Nasarawa State Nigeria to inform HIV prevention programme planning and Implementation. The study was based on the Modes of HIV Transmission (MOT) incidence model recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This is in line with findings from the analyses of new HIV infections in Nasarawa State Nigeria which revealed that close to half of all new HIV infections in the state occur among persons who reported low risk including married partners. 6 The male partners often serve as the bridge between the traditional high risk populations such as sex workers, MSM and injecting drug users and the general population.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with findings from the analyses of new HIV infections in Nasarawa State Nigeria which revealed that close to half of all new HIV infections in the state occur among persons who reported low risk including married partners. 6 The male partners often serve as the bridge between the traditional high risk populations such as sex workers, MSM and injecting drug users and the general population.…”
Section: Discussionmentioning
confidence: 99%